Bibliometric Analysis of Innovation Research in Public Administration - Bran-Piedrahita, Lemy; Valencia-Arias, Alejandro; Palacios-Moya, Lucía; Arias-Vargas, Francisco Javier (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The objective of this work was to identify the main thematic trends in the study of innovation strategies within public administration. For this purpose, a bibliometric analysis was carried out based on articles obtained from the Scopus database, where quantity, quality and structure indicators were calculated. The period 2018 - 2020 was identified with the highest productivity around the subject under study; in addition, quantity and quality indicators reflect a concentration of publications and their citations in industrialized countries such as the United Kingdom, Germany, and Denmark. Thus, it is concluded that studies around the topic in regions such as Latin America should be further explored, since there is a high concentration of specialized literature from the perspective of developed economies.